A Market-based Indicator of Currency Risk: Evidence from American Depositary Receipts - Stefan Eichler; Ingmar Roevekamp (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2016)
We introduce a novel currency risk measure based on American Depositary Receipts (ADRs). Using a multifactor pricing model, we exploit ADR investors' exposure to potential devaluation losses to derive an indicator of currency risk. Using weekly data for a sample of 831 ADRs located in 23 emerging markets over the 1994-2014 period, we find that a deterioration in the fiscal and current account balance, as well as higher inflation, increases currency risk. Interaction models reveal that these macroeconomic fundamentals drive currency risk, particularly in countries with managed exchange rates, low levels of foreign exchange reserves and a poor sovereign credit rating.
urn:nbn:de:gbv:3:2-53151
Keywords: F31; F37; G12; G15; 330; currency risk; currency crises; American depositary receipts; emerging markets